Determination of Cisplatin Cross-Linked Hyaluronic Acid (CPHA) Hydrogel and DNA Using the Fluorescent Response from Mercaptopropionic Acid (MPA) Capped Cadmium Telluride Quantum Dots (CdTe QDs). (13th October 2021) - Jin, Penghui; Ma, Daoqing; Gao, Yabiao; Wang, Libin; Gao, Zhihong; Zhang, Yating; Liu, Mingxin; Xu, Jingying; Wang, Jidong
Abstract: A highly sensitive and dual-directional fluorescent sensing system was developed to detect both cisplatin prodrug cross-linked hyaluronic acid (CPHA) hydrogel (quencher) and DNA (receptor) based on mercaptopropionic acid (MPA) capped CdTe quantum dots (QDs). Different from the previous work for this platinum compound, a multifunctional delivery system, CPHA hydrogel, which was used to address the challenges in drug resistance and severe side effects, was prepared and accurately detected based on the synthesis of the cisplatin prodrug and fluorescence quenching of CdTe QDs resulting from photo-induced electron transfer. When DNA was conjugated with Pt ions in a system composed of CdTe QDs and CPHA hydrogel, the fluorescence of the system was recovered for the determination of DNA. This reversible "turn off–on" strategy presented a high sensitivity and low detection for CPHA hydrogel from 10 to 50 nM with a detection limit of 1.50 nM and DNA from 0 to 75 nM with a detection limit of 0.60 nM. This approach provides a novel direction for further study of the Pt based drug-load with reduced side effects and improved therapy efficacy, effective screening of anticancer drugs, and accurate determination of DNA at low concentrations.